Aktivitas Antibakteri Ekstrak dan Fraksi dari Ekstrak Metanol Daun Manggis (Garcinia mangostana) pada Bakteri Penyebab Ulkus Diabetik - Vivi Rosalina; R Mahendra (Jurnal Surya Medika (JSM), 2021)
Diabetes mellitus (DM) is a degenerative disease due to metabolic disorders with acute to chronic hyperglycemic conditions. The complication of this disease is peripheral neuropathy exacerbated by bacterial infection, causing ulcers (sores) on the feet, hands, knees, back, and other parts of the body. The mangosteen plant (Garcinia mangostana) is empirically believed to have antidiabetic and cure diabetic ulcers. This study aims to compare the antibacterial activity of extracts and fractions of methanol extract of mangosteen leaves at concentrations of 20%, 40%, 60%, 80%, and 100% against the bacteria causing diabetic ulcers in vitro. The research began with the maceration of mangosteen leaf powder extraction using methanol as a solvent. The fractions were obtained by the vacuum liquid chromatography (KCV) method. The bacteria that cause diabetic ulcers are obtained from ulcer specimens of diabetic ulcer patients. Antibacterial activity of extracts and fractions at 5 concentration series was tested using the disc diffusion method with 10% DMSO negative control and positive controls, namely Amoxicillin, Ampicillin, Ciprofloxacin, Cefotaxime, Gentamycin, Erythromycin, and Doxycycline. Antibacterial activity was expressed by the large area of the inhibition zone on the media inoculated with ulcer bacteria and incubated for 24 hours at 370 C. The results showed that there were 5 dominant bacteria found in the diabetic ulcer specimens, namely Escherichia spp, Klebsiella spp, Staphylococcus spp, salmonella spp, and Shigella spp. The results of the antibacterial sensitivity test showed that ciprofloxacin had the largest area of inhibition zone compared to Amoxicillin, Ampicillin, Cefotaxime, Gentamycin, Erythromycin, and Doxycycline so that Ciprofloxacin could be used as a positive control. The results of the antibacterial activity test for the methanol extract of mangosteen leaves with a concentration of 100% produced the largest inhibition zone, namely 27.10 mm ± 0.1 compared to methanol extract, fractions A, B, and C in all concentration series. However, the inhibition zone of the 100% concentration of mangosteen leaves methanol extract was smaller than the positive control of ciprofloxacin 5 μg / disk, which was 35.01 mm ± 0.1.